Low penetrance of a SDHB mutation in a large Dutch paraganglioma family - Jansen Jeroen C; Romijn Johannes A; Morreau Hans; Stokkel Marcel PM; Bonsing Bert A; van Bunderen Patrick A; de Miranda Noel F; Woortman Sanne A; Weiss Marjan M; Hes Frederik J; Vriends Annette HJT; Bayley Jean-Pierre L; et al. (BMC, 2010)
Abstract Background Germline mutations of the succinate dehydrogenase subunit B gene (SDHB) predispose carriers for paragangliomas, and current estimates of the chance of mutation carriers actually developing tumors (penetrance) are high. We evaluate the phenotype and penetrance of a germline SDHB mutation in a large and clinically well-characterized paraganglioma family. Methods Following identification of the mutation in a 31 year old index-patient, extensive clinical screening was performed in mutation carriers to evaluate the presence of head and neck, thoracic and abdominal paragangliomas. Presymptomatic DNA testing was performed in 19 family members. Results DNA analysis detected 14 further SDHB mutation carriers. Three mutation carriers (median age 78 years) declined clinical surveillance, but had no clinical signs or symptoms associated with paragangliomas. The remaining 11 mutation carriers (mean age 53, range 37-76 years) consented to clinical screening. In only two, aged 43 and 48 years, were subclinical vagal paragangliomas identified. Conclusions Only three of the fifteen mutation carriers in this family have developed paraganglioma, which results in a calculated penetrance of 26% at 48 years of age. This figure is lower than current estimates, and we conclude that the co-operation of this family allowed an almost complete attainment of mutation carriers, and the extensive clinical evaluation carried out allowed us to identify all affected individuals.